Galactic archaeology: Understanding the metallicity gradients with chemo-dynamical models. Issue Volume 14:Issue A30(2018) (August 2018) - Minchev, I.; Anders, F.; Chiappini, C.
Abstract: Radial metallicity gradients measured today in the interstellar medium (ISM) and stellar components of disk galaxies are the result of chemo-dynamical evolution since the beginning of disk formation. This makes it difficult to infer the disk past without knowledge of the ISM metallicity gradient evolution with cosmic time. We show that abundance gradients are meaningful only if stellar age information is available. The observed gradient inversion with distance from the disk mid-plane seen in the Milky Way can be explained as the effect of inside-out disk formation and disk flaring of mono-age populations. A novel recent method is presented for constraining the evolution of the Galactic ISM metallicity with radius and time directly from the observations, while at the same time recovering the birth radii of any stellar sample with precise metallicity and age measurements.